2009
DOI: 10.1007/s12306-009-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of parallel pre-contoured plates in the treatment of A and C fractures of the distal humerus

Abstract: The purpose of this study was to retrospectively evaluate the clinical and radiological results of fixation with parallel pre-contoured plates in intra-articular and extra-articular distal humerus fractures. We retrospectively evaluate seven cases of type A and six cases of type C fracture treated with the Mayo Clinic Congruent Elbow Plate system (Acumed, Hillsboro, Oregon) after a mean follow-up of 14.8 and 21.3 months, respectively. Mayo Elbow Performance Score (MEPS) was utilized for functional evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…The mean MEPS score in our study was found to be 88.4; this result was superior to several studies 61617. A study by Rebuzzi et al 18 showed an average score of 94.17 which was higher as compared to our study, but this study had less number of cases ( n = 13). It was a retrospective study in comparison to our study which is a prospective study of 94 cases.…”
Section: Discussioncontrasting
confidence: 93%
“…The mean MEPS score in our study was found to be 88.4; this result was superior to several studies 61617. A study by Rebuzzi et al 18 showed an average score of 94.17 which was higher as compared to our study, but this study had less number of cases ( n = 13). It was a retrospective study in comparison to our study which is a prospective study of 94 cases.…”
Section: Discussioncontrasting
confidence: 93%
“…Multiple level IV series have reported satisfactory results with perpendicular plating techniques [30][31][32][33][34] and parallel plating techniques. [35][36][37][38][39][40] Several biomechanical studies have demonstrated that parallel plate configurations at 180° to each other are biomechanically superior to perpendicular plates when a gap model is used to simulate fracture comminution. [43][44][45] Two clinical level IV studies have reported on the results of locked plating of distal humerus fractures (n = 52 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Level II • 1 study 27 Level III • 2 studies 28,29 Level IV • 20 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] occurs following operative intervention for distal humerus fractures.…”
Section: Quality Of the Evidencementioning
confidence: 99%
“…15 Schmidt-Horloh e et al followed up 51 patients with 52 mainly C-type (75.5%) fractures treated with 2 anatomically preshaped locking plates. 18 Results were excellent or good in 95.5% (Mayo Elbow Performance Score [MEPS], 87.5), mean extension deficit was 10 (11.4 in our study), and a stable fixation providing early physical therapy could be achieved in 73.1% of all fractures (82% in our study).…”
Section: Discussionmentioning
confidence: 99%